Unlocking success: determining predictors of high performance among COMBI community health volunteers in Kuala Lumpur and Putrajaya - Ahmad Fauzi, Fatimah; Mohd Zulkefli, Nor Afiah; Abdul Razak, Muhammad Izmanuddin Fitri (Tehran University of Medical Sciences, 2024)
Background: Community Health Volunteers (CHVs) are crucial in achieving universal health coverage and vital in public health activities, including the COMBI (Communication for Behavioral Impact) approach for dengue prevention and control and assessing the performance of COMBI CHVs are essential in evaluating the program effectiveness. This study aims to measure the level of performance and determine predictors of high-performance among COMBI CHVs in Kuala Lumpur and Putrajaya. Methods: A cross-sectional study was conducted among 285 COMBI CHVs from 5 health operational zones in Kuala Lumpur and Putrajaya. The CHVs were stratified proportionately, with 45.5% of respondents randomly selected from each stratum based on their zones. Self-administered questionnaires assessed their performance level and associated factors, including training, supervision, knowledge, motivation, and job satisfaction. Chi-square and Multiple Logistic Regression tests were used to determine the factors and predictors of high-performance COMBI CHVs. Results: The prevalence of high-performance COMBI CHVs was 59.3%, significantly associated with training factors (experience, duration, and adequacy of training), supervision factors (being supervised, supervision frequency, and encouragement from supervision), motivation and job satisfaction level. As for significant predictors, having at least one day of training (AOR=14.557), being supervised by medical personnel (AOR=4.997), having a high motivation level (AOR=5.538) and having a high job satisfaction level (AOR=4.562) were more likely to have a high-performance level. Conclusion: Training duration, supervisor background, motivation and job satisfaction can contribute to high-performance levels among COMBI CHVs, which can applied in evidence-based policies and strategies for performance improvement and more effective community healthcare delivery.